DAMPAK PROGRAM KELUARGA HARAPAN TERHADAP PENINGKATAN KESEJAHTERAAN MASYARAKAT (Studi Kasus Di Kelurahan Sekip Kecamatan Limapuluh Kota Pekanbaru) - Dhimas Haryato; Syamsul Bahri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT Since the New Order era until now, there have been many and various poverty alleviation programs carried out by the Government of Indonesia. However, it is difficult to conclude whether the number of poor people is decreasing or increasing. This is because depending on the poverty parameter used by many parties, it also varies. The Program Keluarga Harapan (PKH) Non-Cash Social Assistance Program is one of the social protection programs that aims to reduce the burden of spending and increase the income of poor and vulnerable families which has been going on since 2017 until now. This research is intended to answer the problem of how PKH impacts on people's welfare? The research was conducted in urban areas, namely Sekip Village, Limapuluh District, Kota Pekanbaru. Theory Sociology used is about poverty and empowerment concepts and the method used is descriptive qualitative by specifying that the informants consist of poor and vulnerable beneficiary families, social assistants and other related government elements. The research results show that the impact of the program in general has not yet shown any change in the behavior of beneficiary families to adopt an independent lifestyle so that they are able to access various health, education and social welfare services. Continuity of education for school-age children can be achieved, as well as an increase in family income from social assistance funds received. However, because self-sufficiency has not grown, aid funds cannot be developed productively to improve family welfare. The factors caused is such social assistants are less intensive and behavior change poors and susceptibles takes a long time and is intensive in an integrated program of stake-holders. Keywoords: Impact, Program Keluarga Harapan, and Community Welfare.